Supply Chain Management, Sustainability, Performance and Technology: A Bibliometric Analysis - Talmoudi, Ramzi (Journal of Cultural Analysis and Social Change, 2025)
The current study undertakes a quantitative bibliometric approach to examine a global research landscape on Supply Chain Management, Sustainability, Performance, and Technology. emerging research themes using keywords clustering are explored and underexplored themes are uncovered. Only 659 articles from the Clarivate Analytics Web of Science database are considered The search strategy included the terms (((TS=("Supply Chain Management" )) AND TS=(Sustainability)) AND TS=(Performance)) AND TS=(Technology).keywords clustering revealed most prominent topics as " blockchain applications for supply chain management sustainability", " technology driven sustainability" . This study highlights literature gaps advocated mainly to industry 4.0 technologies long-term sustainability implications and trade-offs in sustainable supply chain practices of blockchain technology. Technological advancement alone does not adequately address sustainability challenges related to environmental, social, and economic sustainability objectives. The originality of the problem is attracting increasing attention from researchers and industry professionals, as evidenced by the large number of recent bibliometric studies on this topic. However, the topic of this article has not yet been addressed.